Restructuring in a South Africa city during transition : urban development and transformation in Pietersburg during the 1990s - Donaldson, Sybrand Eloff (Stellenbosch : Stellenbosch University, 2012)
Thesis (D.Phil.) -- University of Stellenbosch, 1999.